Kinetic Mechanism of the ssDNA Recognition by the Polymerase X From African Swine Fever Virus. Dynamics and Energetics of Intermediate Formations - Jezewska, Maria J. (2011)
Kinetic mechanism of the ssDNA recognition by the polymerase X of African Swine Fever Virus (ASFV) and energetics of intermediate formations have been examined, using the fluorescence stopped-flow method. The association is a minimum three-step process [Formula: see text] The nucleic acid makes the initial contact through the C-terminal domain, which generates most of the overall ΔG°. In the second step the nucleic acid engages the N-terminal domain, assuming the bent structure. In equilibrium, the complex exists in at least two different states. Apparent enthalpy and entropy changes, characterizing formations of intermediates, reflect association of the DNA with the C-terminal domain and gradual engagement of the catalytic domain by the nucleic acid. The intrinsic DNA-binding steps are entropy-driven processes accompanied by the net release of water molecules. The final conformational transition of the complex does not involve any large changes of the DNA topology, or the net release of the water molecules.